Comparison of the Pharmacokinetic Properties of Triamcinolone and Dexamethasone for Local Therapy of the Inner Ear - Salt, Alec Nicholas; Hartsock, Jared James; Hou, Jennifer; Piu, Fabrice (Frontiers in Cellular Neuroscience, 2019)
Some forms of triamcinolone may provide alternate options for local therapy of the inner ear in addition to the steroids currently in use. We compared the perilymph pharmacokinetics of triamcinolone-acetonide, triamcinolone and dexamethasone, each delivered as crystalline suspensions to guinea pigs. Triamcinolone-acetonide is a widely used form of the drug with molecular properties that allow it to readily permeate biological barriers. When applied intratympanically triamcinolone-acetonide entered perilymph rapidly but was also found to be eliminated rapidly from perilymph. The rapid rate of elimination severely limits the apical distribution of the drug when applied locally, making it unsuitable for use in the ear. In contrast, triamcinolone, rather than triamcinolone-acetonide, is a more polar form of the molecule, with higher aqueous solubility but calculated to pass less-readily through biological boundaries. Perilymph concentrations generated with intratympanic applications of triamcinolone were comparable to those with triamcinolone-acetonide but elimination measurements showed that triamcinolone was retained in perilymph longer than triamcinolone-acetonide or dexamethasone. The slower elimination is projected to result in improved distribution of triamcinolone towards the cochlear apex, potentially allowing higher drug levels to reach the speech frequency regions of the human ear. These measurements show that triamcinolone could constitute an attractive additional treatment option for local therapy of auditory disorders.